Practice of balanced scorecard implementation and its contributing factors among public primary hospital professionals in Central Gondar zone, Northwest Ethiopia - Yeshaw, Seid; Asrade, Geta; Hagos, Asebe; Chanie, Muluken Genetu; Worku, Nigusu (Frontiers in Public Health, 2025)
BackgroundGlobally, a Balanced Scorecard (BSC) is used to measure healthcare institutional performance. Thus, since 2010, Ethiopia has adopted and implemented BSC in all its civil service organizations. Ineffective implementation of this tool has a significant impact on the healthcare performance. The health sector’s healthcare provision, customer satisfaction, customer retention, organizational profit, changes and improvements in the healthcare delivery practice are affected by the implementation of BSC tools. However, no evidence or study indicates the implementation of BSC practice in the Ethiopian context. Thus, this study aimed to assess the magnitude of BSC implementation practice and associated factors among healthcare providers at public primary hospitals in the Central Gondar zone, Northwest Ethiopia.MethodsA mixed methods study was carried out at public primary hospitals from May 25 to June 26, 2022, in Central Gondar zone with 404 study participants. Study participants were selected using a systematic random sampling technique for the quantitative part, and 12 study subjects were chosen purposively for the qualitative part. Bi-variable and multivariable logistic regression analyses were done. The strength of associations was measured using the adjusted odds ratio (AOR) at 95% CI and a p-value of less than 0.05 in the multivariable analysis to declare significant factors. Thematic analysis was applied for the qualitative data using open code 4.03 version software.ResultsThe implementation practice of BSC was found at 48.5% (95% CI: 43.6, 53.4%) with a response rate of 95.28%. Teamwork (AOR: 2.68, 95% CI; 1.53, 4.69), organizational communication (AOR: 3.24, 95% CI: 1.79, 5.89), and availability of infrastructure (AOR: 2.03, 95% CI; 1.14, 3.64) were significantly associated to balanced scorecard implementation practice.ConclusionThe implementation practice of BSC was poor compared to the national standard and the findings of prior studies. Thus, concerned stakeholders need to focus on improving and working on organizational communication channels, teamwork, and infrastructure fulfilment to facilitate the implementation practice of a balanced scorecard.